Use of Rectangular Grid Miniplates for Fracture Fixation at the Mandibular Angle - Hochuli-Vieira, Eduardo [UNESP]; Thi Khanh Linh Ha; Pereira-Filho, Valfrido Antonio [UNESP]; Landes, Constantin Alexander (W B Saunders Co-elsevier Inc, 2011)
Purpose: The aim of this study was to evaluate the clinical outcome of patients with mandibular angle fractures treated by intraoral access and a rectangular grid miniplate with 4 holes and stabilized with monocortical screws.Patients and Methods: This study included 45 patients with mandibular angle fractures from the Department of Oral and Maxillofacial Surgery São Paulo State University, Araraquara, Brazil, and from the Clinic of Oral and Maxillofacial Surgery at the University of Frankfurt, Germany. The 45 fractures of the mandibular angle were treated with a rectangular grid miniplate of a 2.0-mm system by an intraoral approach with monocortical screws. Clinical evaluations were postoperatively performed at 15 and 30 days and 3 and 6 months, and the complications encountered were recorded and treated.Results: The infection rate was 4.44% (2 patients), and in 1 patient it was necessary to replace hardware. This patient also had a fracture of the left mandibular body; 3 patients (6.66%) had minor occlusal changes that have been resolved with small occlusal adjustments. Before surgery, 15 patients (33.33%) presented with hypoesthesia of the inferior alveolar nerve; 4 (8.88%) had this change until the last clinical control, at 6 months.Conclusions: The rectangular grid miniplate used in this study was stable for the treatment of simple mandibular angle fractures through intraoral access, with low complication rates, easy handling, and easy adjustment, with a low cost. Concomitant mandibular fracture may increase the rate of complications. This plate should be indicated in fractures with sufficient interfragmentaty contact. (C) 2011 American Association of Oral and Maxillofacial Surgeons J Oral Maxillofac Surg 69:1436-1441, 2011